Impaired Sensorimotor Integration in Restless Legs Syndrome - Lin, Yicong; Wang, Yijin; Zhan, Shuqin; Ding, Yan; Hou, Yue; Wang, Li; Wang, Yuping (Frontiers in Neurology, 2018)
Objective: Restless legs syndrome (RLS) is a complicated sensorimotor syndrome that may be linked to changes in sensorimotor integration. The mechanism of such changes is unclear. The aim of this study was to investigate sensorimotor integration in patients with RLS through transcranial magnetic stimulation-motor evoked potentials (TMS-MEPs) preceded by peripheral electric stimulation. Methods: Fourteen RLS patients and 12 healthy, age-matched controls were investigated. The clinical severity of RLS was evaluated based on the International Criteria of the International Restless Legs Syndrome Study Group (IRLSSG) severity scores. The tibial and median H-reflexes and the resting motor threshold (RMT) of the abductor pollicis brevis (APB) were tested in all 26 subjects. The RMT of the tibialis anterior (TA) was tested in 8 patients and 7 controls. All 26 subjects underwent measurement of unconditioned MEPs of the APB. Electric pulses were applied to the right median nerve, followed by TMS pulses over the left motor cortex at interstimulus intervals (ISIs) of 20, 25, 30, 50, 100, 150 and 200 ms. Unconditioned MEPs of the TA were measured in 8 patients and 7 controls. Electric pulses were applied to the right peroneal nerve, followed by TMS pulses over the left motor cortex at ISIs of 30, 35, 45, 60, 100 and 200 ms. The degree of modulation of MEPs by electric stimulation was expressed as the ratio of the conditioned MEP amplitude to the unconditioned MEP amplitude. Ratios <1 indicated inhibition, and ratios >1 indicated facilitation. Results: No significant differences in RMT or H-reflex latencies or amplitudes were found between RLS patients and controls. A significant increase in unconditioned MEP amplitudes of the TA was observed in patients compared to controls (p=0.03). Long-latency afferent inhibition (LAI) of the median nerve in RLS patients was decreased significantly at ISIs of 150 (p=0.000) and 200 ms (p=0.004). Upon peroneal nerve stimulation, no significant difference was observed between the two groups at any ISI. Conclusions: Our results suggest increased motor cortical excitability of the legs and disturbed sensorimotor integration in RLS patients; this disturbance might originate at the cortical level.